The Influence of Financial Performance Q3 2023 Through Net Profit Margin (NPM), ROA and ROE on the Decrease in Share Prices of PT Herbal Medicine and Pharmaceutical Industry Sido Muncul Tbk - Supandi, Denny; Afriyeni, Afriyeni (Ridwan Institute, 2023)
The purpose of this study is to determine the effect of Net Profit Margin (NPM), Return On Asset (ROA), and Return On Equity (ROE) on the decline in share prices at PT. Sido Muncul Tbk. Herbal and Pharmaceutical Industry which is listed on the Indonesia Stock Exchange for the 2023 period. This type of research is descriptive quantitative. The population in the study is the financial statements and stock prices of PT. Sido Muncul Tbk's Herbal and Pharmaceutical Industry for the 2023 period. In this study, purposive sampling techniques were used, the samples in this study were financial statements and stock prices for the quarter of 2023. Researchers use documentation observation techniques, analytical tools used using multiple linear regression analysis. The results stated that partially Net Profit Margin (NPM) and Return On Asset (ROA) did not have a significant effect on the decline in share price at PT. Sido Muncul Tbk. Herbal and Pharmaceutical Industry While Return On Equity (ROE) has a significant effect on the decline in share price at PT. Sido Muncul Tbk. Herbal and Pharmaceutical Industry Simultaneously Net Profit Margin (NPM), Return On Asset (ROA), and Return On Equity (ROE) have a significant effect on the decline in share price at PT. Herbal and Pharmaceutical Industry Sido Muncul Tbk.